Weblab of a control experiment in a newborn baby incubator - Bauer, Karine; Mendes, Luciano Antonio (2015 12th International Conference on Remote Engineering and Virtual Instrumentation (REV), 2015)
WebLabs, or Remotely Operated Laboratories, allow for remote control and monitoring of interactive or batched systems with educational objectives. Considered as additional resources in education, they contribute to a flexible learning model and make possible for students to perform laboratory experiments remotely, off-class, in collaboration, thus contributing to the reduction of laboratory equipment idleness. The purpose of this paper is to report steps in designing and enabling a WebLab with background theme on the control and monitoring of thermal comfort parameters in a newborn baby incubator. Three didactical experiments can be performed in this WebLab: transfer function evaluation, on-off control and PID controller tuning, with users challenged to optimally tune the parameters of a controller algorithm. In the end of the session, the user can enter his/her impressions regarding the WebLab usage by answering a questionnaire. The WebLab design includes the evaluation of students' abilities through performance indexes while keeping operation within the requirements of an associated medical safety standard. A systematic approach for the WebLab design process has been employed, with the system design split in three layers: physical system, hardware and software. Sets of qualitative and quantitative requirements to be attended were defined. System and product design techniques, such as House of Quality, Morphological Matrix and Pugh's Method, have been employed to address the conversion of the project requirements into the Weblab overall solution. Virtual Instrumentation resources have been used to acquire temperature, humidity and air speed signals. The LabVIEW platform was used to support experiment integration and to create the user interface using LabVIEW Remote Panel architecture. The WebLab has been successfully implemented and presently can be accessed within the university network.